Faktor Risiko yang Dapat Diubah pada Demensia Lansia: Ulasan Literatur Naratif Singkat - Hatimi, Fahmi Ilham; Hardiansyah, Ridwan; Islami, Suryadi (Medula, 2025)
The gradual neurological disease known as dementia causes a substantial reduction in cognitive function, which impairs an older person's capacity to carry out everyday tasks on their own. Dementia is a serious worldwide health concern since its prevalence rises with age. Through a narrative literature review, this study seeks to uncover modifiable risk factors for dementia in the elderly. Utilizing the terms "dementia risk factors," "factors of dementia," and "dementia in elderly," information was obtained from databases including Google Scholar, Garuda, and NCBI. The results show that reducing alcohol intake, quitting smoking, managing diabetes mellitus, and engaging in regular physical activity are all effective ways to avoid dementia. Increased cerebral blood flow from exercise supports cognitive function and slows the progression of dementia. Quitting smoking and drinking less alcohol reduces oxidative stress, inflammation, and neurotoxic damage—all of which hasten the onset of neurodegenerative diseases. Controlling diabetes helps avoid hypoxia and vascular damage, both of which can worsen cognitive impairment. These lifestyle changes not only lessen the risk of dementia but also greatly lessen the financial, social, and emotional strain on people, families, and communities. This article highlights the value of early intervention through lifestyle modifications and how it can enhance older people's overall quality of life. It offers practical advice on how to lessen the effects of dementia, one of the most important health issues of our time.